Cephalopods of the San José Formation of Peru (Floian, Early Ordovician) and their paleogeographic significance - Kröger, Björn (2024)
Fossil remains of extinct relatives of cephalopods are known to occur in Peruvian strata of Ordovician age (~485–444 million years old) for a long time. However, they remain poorly known today. Here, we describe for the first time specimens that were collected from strata of the San José Formation of the Kimbiri and Inambari areas, southeastern Peru. The assemblage contains five species; one of them, Bactroceras cocafolium, is new to science. One other species is known from strata of the same age from elsewhere in the central Andes. The five species also show a relationship with cephalopod assemblages known from the old continents Gondwana and Avalonia.